Performance Measurement of the Companies in the Indian Steel Industry - Mary Jeana Ilango, Dr. Chetan Panse (International Journal of Advanced Science and Technology, 2020)
This paper presents the performance measurement of four different companies in the Indian Steel Industry. The domestic availability of raw materials such as cost-effective labour and iron ore has led to the growth in the Indian steel sector. Tata Steel is the second in the world as the most geographically diversified steel producer and they are based in Jamshedpur, Jharkhand. JSW Steel is the second biggest private steel producing firm in India and they are based in Mumbai, Maharashtra. Steel Authority of India Limited is a public sector company and is the biggest steel producing corporation in India and they are located near the raw materials – eastern and central India. Jindal Steel and Power produces steel and power from their confined coal and iron ore mines through backward integration. The tool used for the comparison is Data Envelopment Analysis. It is a linear programming tool which utilizes a Performance Measurement technique used for comparing the performances of similar units of different organizations. The input variable is the Inventory Turnover Ratio and the output variable considered for the comparison is profitability. The financial parameters considered were Return on Equity (ROE), Return on Assets (ROA), which act as indicators of profitability of an organization and liquidity parameters like Quick Ratio and Current Ratio. An analysis of the performance of the above stated companies has been made by comparing them with one another with respect to the industry.